THEORETICAL ANALYZING AND MODELING FOR ELECTROMAGNETIC VIBRATION OF PERMANENT MAGNET SYNCHRONOUS MOTOR - LI Liang; JIANG YuChen (Jixie qiangdu)
Permanent magnet synchronous motor（ PMSM） having the following characteristics of high efficiency,high stability,long using life and simple maintenance is one of the important development directions in the motor field. The research on electromagnetic vibration is foundations of designing the low noising PMSM. The structure of PMSM is introduced. The models of air gap magnetic ux density,the radial electromagnet force and structural vibration are developed. The factors effecting electromagnetic vibration are theoretical analyzed,the frequencies of electromagnetic vibration are given. The simulation results show the PMSM produces severe vibration with frequency of 2,4 and 6 times fundamental frequency,when the number of slot near to 2,4,6 and 8 times the number of poles. These efforts provide references for designing different type of permanent magnet synchronous motor.